2018
DOI: 10.1002/cpp.2321
|View full text |Cite
|
Sign up to set email alerts
|

Do clinical experience, formal cognitive behavioural therapy training, adherence, and competence predict outcome in cognitive behavioural therapy for anxiety disorders in youth?

Abstract: Therapist adherence, competence, and clinical experience are associated with outcomes of manualized CBT for youth anxiety disorders, but mixed findings indicate the need for more research in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
3
5
0
Order By: Relevance
“…We found significant overlap between adherence and competence, which is consistent with previous studies with this instrument (Bjaastad et al, 2018;Harstad et al, 2021). However, other studies focused on CBT for youth anxiety have found less overlap (rs 0.55-0.65; McLeod et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We found significant overlap between adherence and competence, which is consistent with previous studies with this instrument (Bjaastad et al, 2018;Harstad et al, 2021). However, other studies focused on CBT for youth anxiety have found less overlap (rs 0.55-0.65; McLeod et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has found correlations between adherence and competence ranging from 0.30 (Carroll et al, 2000) to 0.96 (Barber et al, 2003). The correlations tend to be higher when the same coders score adherence and competence (e.g., Barber et al, 2003;Bjaastad et al, 2018) as opposed to when independent coders score the two components (e.g., McLeod et al, 2018). Our findings suggest that it may be difficult, even for expert coders, to distinguish between adherence and competence.…”
Section: Discussionmentioning
confidence: 41%
See 3 more Smart Citations